Behaviour of non-loadbearing tabique wall subjected to fire – Experimental and numerical analysis. (January 2017) - Ferreira, Débora M.; Araújo, Alexandre; Fonseca, Elza M.M.; Piloto, Paulo A.G.; Pinto, Jorge
Abstract: Tabique construction is one of the most used traditional building techniques and it can be found almost everywhere in Portugal with special incidence in the northeast region. Tabique construction elements can be described as a timber structure filled on both sides with an earth-based render. Tabique elements can be found in ancient buildings, from simple construction as rural dwellings to more urban sophisticated ones. This paper presents a study of the behaviour of tabique walls, concerning its fire resistance. Therefore, an experimental analysis was performed using tabique wall panel specimens. Such wall panels were made in pine wood with an earth-based render finishing. In order to assess the thickness effect of the earth-based render on the fire resistance of the wall, three specimens with different render thicknesses of 15 mm, 10 mm and 5 mm were tested in a fire-resistance furnace according to the ISO 834[1] standard fire curve. Fire resistance is a measure of the ability of a building element to resist a fire, usually the time for which the element can meet appropriate criteria during exposure to a standard fire resistance test. By this way it is possible to increase the safety of people and property. Two performance criteria were verified which are the integrity and the insulation. In addition, a numerical model was also developed in order to assess the tabique wall behaviour under fire conditions, which was validated using the obtained experimental results. Highlights: First research related to fire behaviour of tabique wall. The insulation criterion was verified on tabique wall exposed to fire. The integrity criterion was verified as no flame or ignitions have been identified. The earth-based render significantly improved the fire resistance. The numerical model show good agreement with the experimental results.